2012
DOI: 10.4304/jltr.3.4.793-800
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking and Iranian EFL Context

Abstract: Abstract-The advent of the information diffusion emanating from the information technology of the third millennium along with the revamped concept of literacy and intellectual understanding, and the demand for accountability as one of the prerequisites of modern societies has given birth to a movement resting on the idea that schools should be less concerned with imparting information and requiring the memorization of empirical data. Dealing with the extraordinary challenges of today's information society requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…In order to help learners to foster their CT and decision making ability, it is necessary for teachers to educate themselves ideally and be aware of their enormous responsibility in the classroom. In addition, to hold in-service training classes to sharpen teachers CT skills and improve their teaching techniques is of great importance in language learning setting (Fahim & Ahmadian, 2012).On the other hand, in order to improve teachers' capability for teaching CT, schools and institutions must provide them with required time and resources which are necessary for professional development to occur. By incorporating CT teaching in different classes, the educational program will produce the educated people who are able to make decisions more accurately and solve problems more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…In order to help learners to foster their CT and decision making ability, it is necessary for teachers to educate themselves ideally and be aware of their enormous responsibility in the classroom. In addition, to hold in-service training classes to sharpen teachers CT skills and improve their teaching techniques is of great importance in language learning setting (Fahim & Ahmadian, 2012).On the other hand, in order to improve teachers' capability for teaching CT, schools and institutions must provide them with required time and resources which are necessary for professional development to occur. By incorporating CT teaching in different classes, the educational program will produce the educated people who are able to make decisions more accurately and solve problems more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the self-regulation of EFL learners find out near 53 percent of the achievement of language but the CT of EFL learners find nearly 28 percent of the achievement of language. Fahim and Rezanejad (2014) considered the critical thinking in the EFL context of Iran. Hassani, Rahmani and Babaei (2013) investigated the relationship between Iranian EFL learners' critical thinking and reading comprehension performance in journalistic texts.…”
Section: B Ct and Translation Of Literary Textsmentioning
confidence: 99%
“…The critical thinking skills are (1) reasoning, (2) comprehension, application, analysis, and synthesis, (3) interpretation, (4) judgment, and (5) evaluation. Adopting a cognitive perspective to critical thing and in an attempt to revise Bloom's taxonomy of educational objectives, Consequently, according to Fahim and Ahmadian (2012), developing students' evaluative and reflective skills are not well-regarded. Moreover, as Jalilifar (2010) pointed out, "despite the growing interest in learning English as a foreign language in Iran, students at college level seem rarely proficient enough to read and comprehend English language texts" (p. 98).…”
Section: Introductionmentioning
confidence: 99%